1982
DOI: 10.1002/ccd.1810080314
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac perforation with tamponade during cardiac catheterization

Abstract: Among 6,675 adult patients undergoing cardiac catheterization in our institution, three patients developed cardiac perforation and tamponade (incidence 0.04%). Two perforations involved the left atrium, and one the right atrium. Tamponade developed in the three patients. Hemodynamic confirmation of tamponade was available in two patients. Pericardiocentesis was performed in all three patients. Two patients required emergency surgery. All patients recovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Tamponade necessitated pericardial drainage in four (0.03 %) [4]. Geld et a1 found that three out of 6,675 patients (0.04%) undergoing cardiac catheterization developed cardiac tamponade requiring drainage [5]. Right ventricular perforation from right heart catheterization may be much more frequent than these figures suggest since clinical manifestations may not be apparent.…”
Section: Discussionmentioning
confidence: 96%
“…Tamponade necessitated pericardial drainage in four (0.03 %) [4]. Geld et a1 found that three out of 6,675 patients (0.04%) undergoing cardiac catheterization developed cardiac tamponade requiring drainage [5]. Right ventricular perforation from right heart catheterization may be much more frequent than these figures suggest since clinical manifestations may not be apparent.…”
Section: Discussionmentioning
confidence: 96%
“…9 Gehl et al reported three cardiac perforations during diagnostic cardiac catheterization among 6675 patients, perforation sites were the left atrium in two patients and right atrium in one patient. 10 Keltai et al described four cases of cardiac perforation in 11000 procedures; one at the left atrium and three in the right ventricle. 11 The incidence of perforation is clearly related to the performance of procedures that use stiffer catheters (transseptal catheterization, endomyocardial biopsy, balloon valvuloplasty, needle pericardiocentesis, and placement of NIH or temporary pacing catheters).…”
Section: Discussionmentioning
confidence: 98%
“…Unintentional perforation of the aorta or right atrial free wall may occur and lead to cardiac tamponade. Perforation can also occur with the use of other catheters that are relatively stiff, such as the National Institute of Health angiographic catheter [50]. When perforation occurs and tamponade is suspected, pericardiocentesis is indicated.…”
Section: Coronary Angiography and Uentriculographymentioning
confidence: 96%
“…When perforation occurs and tamponade is suspected, pericardiocentesis is indicated. Cardiac surgery may be necessary [50].…”
Section: Coronary Angiography and Uentriculographymentioning
confidence: 99%